The Psychological Effects of Diabetes Patients' Educational Experience on Health and Food Literacies in Korean - Young Hee Nam (Journal for ReAttach Therapy and Developmental Diversities, 2023)
This study aimed to provide basic data and policy suggestions to improve the health and nutrition level of diabetic patients by identifying the influencing factors on health literacy and food literacy according to diabetes management education experience. This study selected 28,477 (12.4 %) of the 229,242 2021 Community Health Survey subjects diagnosed with diabetes by a doctor. Data were analyzed using the SPSS 26.0 program. In the diabetes management education group (experienced group), there were 11% more males than females. The experienced group was younger and had a higher education level. Having a spouse or a higher BMI value resulted in a higher distribution. The experienced group had a high understanding of nutrition labels and a high food literacy reading comprehension, while the non-experienced group lacked food literacy understanding. The experienced group had a high experience of fundoscopy, while the non-experienced group did not. Diabetes management education experience positively correlated with diabetes treatment methods, health literacy, and food literacy. Weight control experience negatively correlated with diabetes treatment methods, health literacy, and food literacy. Age, education level, occupation, weight control experience, health literacy, food literacy, and diabetes treatment methods were found to be influential factors in the educational experience of diabetic patients. The educational experience of the diabetic patients with an understanding of health literacy was 1.295 times higher than the educational experience of the diabetic patients that lacked an understanding of health literacy. The educational experience of the diabetic patients with an understanding of food literacy was 1.341 times higher than the educational experience of the diabetic patients that lacked an understanding of food literacy. Regarding the diabetes treatment methods, the educational experience of the diabetic patients with 3¬¬–6 methods was 2.576 times higher than the educational experience of the diabetic patients with 0–2 methods. Therefore, managing diabetic patients can mitigate the disease and prevent progression to complications by actively implementing relevant education and increasing the understanding of health literacy and food literacy